JMC528 : Design method / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
The course introduces the students to the real practice of design process that stimulate the idea generation in metal design, design solutions, technical skills of research and communication presentation.